PENGEMBANGAN MULTIMEDIA INTERAKTIF MENGGUNAKAN LECTORA INSPIRE PADA MATERI BUNYI DAN SIFATNYA Pendekatan Research And Development (R&D) Pada Siswa Kelas V Sekolah Dasar Negeri Cibungbulang 01 Kabupaten Bogor Semester Genap Tahun Ajaran - Dewi Simatupang; Nurlinda Safitr; Tatang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research uses a Research and Development (R&D) approach. This research was carried out at Cibungbulang 01 State Elementary School, Bogor Regency in the even semester of 2025/2026 with 23 students. The instruments used in this study consisted of expert validation sheets, student response questionnaires, and teacher response questionnaires to interactive multimedia using lectora inspire on sound materials and their properties. This data analysis technique consists of qualitative data about the results of interviews and quantitative data about the results of validation regarding the results of expert validation, student responses, and teacher responses. The results of the study showed that interactive multimedia using lectora inspire in grade V of SD Negeri Cibungbulang 01 Bogor Regency in learning based on the average assessment of media expert validation 97.3%, the average validation score of linguists 97.3%, and the average validation score of material experts 84%. The validation results are included in the category of "very feasible" to be used strengthened with an N-Gain value of 0.75%. The results of the student response of 88.0% and the teacher's response of 100% are included in the "very feasible" category. Thus, it can be concluded that interactive multimedia using lectora inspire is very valid and very feasible to be used in science and science learning.